Upaya Peningkatan Hasil Belajar Biologi Dengan Menerapkan Model Pembelajaran Discovery Learning Terpadu - Prasetyo, Faisal Imam; Lenggono, Budi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2024)
The purpose of this study was to determine the improvement of learning outcomes of students in class X MIPA 1 in Integrated Islamic High School of Nurhidayah Sukoharjo by applying the Discovery Learning “TERPADU” model in online learning. This research is a classroom action research model of Kemmis and Taggart which consists of four stages in each action, namely planning, implementation and observation, evaluation, and reflection. The research was conducted in two cycles of action. The subjects of this research were students of class X MIPA 1 with a total of 34 students. This research instrument is in the form of tests and non-tests. The results of this study indicate the achievement of student learning outcomes that have increased from pre-action to cycle I to cycle II, namely: (1) the student's average score of 66.68 (pre-action) increased to 82.72 (cycle I) then increased again to 89.11 (cycle II), (2) the percentage of classical completeness of 51.67% (pre-action) increased to 82.33% (cycle I) then increased again to 100% (cycle II), (3) N-gain of 0.31 in the “medium” category (cycle I) increased to 0.58 or stayed in the “medium” category (cycle II). Based on these results, it can be concluded that the application of the Discovery Learning “TERPADU” model can improve Biology learning outcomes. Based on this study, the researcher provides suggestions: (1) this Discovery Learning “TERPADU” model also needs to be tested in other class action research either conducted in online mode or offline mode (in the classroom) and (2) this research needs to be developed by using information technology and computer-based learning media in offline mode learning.